Essays in Honor of Carl G. Hempel
IX, 274 p.
Keywords: The eminent philosopher of science Carl G. Hempel, Stuart Professor of Philosophy at Princeton University and a Past President of the American Philosophical Association, has had a long and distinguished academic career in the course of which he has been professorial mentor to some of America's most distinguished philosophers. This volume gathers together twelve original papers by Hempel's students and associates into a volume intended to do homage to Hempel on the occasion of his 65th year in 1970. The papers are grouped around the unifying topic of Hempel's own interests in logic and philosophy of science, the great majority dealing with issues on inductive logic and the theory of scientific explanatio- problems to which Hempel has devoted the bulk of his outstandingly fruitful efforts. With the approach of 'Peter' Hempel's 65th birthday, an editorial committee sprang into being by an uncannily spontaneous process to prepare to commemorate this event with an appropriate Festschrift. The editors were pleased to receive unfailingly prompt and efficient coopera tion on the part of all contributors. The responsibility of seeing the work through the press was assumed by Nicholas Rescher. The editors are grateful to all concerned for their collaboration. ALAN ROSS ANDERSON PAUL BENACERRAF ADOLF GRUNBAUM GERALD J. MASSEY NICHOLAS RESCHER RICHARD S. RUDNER TABLE OF CONTENTS PREFACE V PAUL OPPENHEIM: Reminiscences of Peter 1 w. v. QUINE: Natural Kinds 5 JAAKKO HINTIKKA: Inductive Independence and the Paradoxes of Confirmation 24 WESLEY c.